Nurse Practitioners’ Practice Patterns in Primary Care in Finland: A Descriptive Qualitative Study - Ruwang Han; Melanie Rogers; Sofia Asplund; Lisbeth Fagerström (Global Qualitative Nursing Research)
Healthcare demands continue to increase across the globe, Advanced Practice Nurses (APNs) including Nurse Practitioners (NPs) are recognised as a valuable workforce that can increase access and improve the quality of care. However, NPs are underrepresented in Finland. This study explored Finnish NPs’ practice patterns and identified the common visit types to NP clinics in primary care. This descriptive qualitative study is part of a multiple-method and action research project that aims to develop and evaluate advanced practice nursing models in primary care within a wellbeing services county of Western Finland. Responses to open-ended questions and interview data from 16 NPs working in primary care were analysed using inductive content analysis. The findings highlight key aspects of NPs’ work, including the types of patients they care for—those with both acute and long-term health needs—and the core elements of their practice, such as conducting health assessments, providing counselling and coaching, engaging in collaborative care, and prescribing medications. The analysis also revealed persistent ambiguity surrounding certain aspects of NP practice. Overall, the findings indicate that NPs in Finland utilise a wide range of knowledge and skills to care for patients presenting with acute and long-term health problems.